Accurate Loss Tangent Determination in Damped Alternating Voltage Tests - Yutthagowith, Peerawut; Chaisiri, Punyavee; Paophan, Busayapol (My University, 2024)
Underground cables are crucial for sustainable energy systems due to their minimal visual impact, reliability, and resilience against weather-related disruptions. As reliance on renewable energy sources rises, their importance grows. Regular evaluation of these cables is essential for ensuring safety, reliability, and resilience of electricity networks. By promptly identifying risks like insulation degradation, utilities can optimize maintenance, prioritize repairs, and bolster the integration of renewables, enhancing overall infrastructure performance. Loss tangent is the most significant value used for evaluation of the cable condition. This paper presents an alternative method for estimation of loss tangent in comparison with a conventional approach in damped alternating current voltage (DACV) tests. In the loss tangent estimation, the equivalent circuit of the DACV test system and a damping factor of the measured test voltage are utilized in the loss tangent estimation. From simulation experimental results, it is found that the conventional method is not accurate in loss tangent estimation in cases of low loss tangent measurement in the range of 0.1% which is a typical value of the new and used underground power cables. However, the accuracy of the proposed method is still in the acceptable range for estimation of the loss tangent in the range of 0.1%
Keywords: damped alternating voltages; equivalent circuit; loss tangent; on-site tests; underground power cable